PENGARUH UMUR DAUN PALA DAN JENIS PENGERINGAN TERHADAP SIFAT KIMIA DAN ORGANOLEPTIK TEH HERBAL DAUN PALA - Maya Lestari; Erna Rusliana Muhammad Saleh; Hamidin Rasulu (Universitas Khairun, 2018)
The purpose of this study for knowing the influnces by ege of nutmeg’s leaf and the type of drying are used to chemical and organoleptic properties of herbal tea by nutmeg’s leaf that produced. This study uses a randomized’s cluster design (RAK) factorial. Principal variable in this research is the analysis of chemical properties (antioxidant, moisture content, ash content, and crude fiber) and organoleptic (taste, color and smell).the old nutmeg’s leaf and the young with two drying type have chemical properties, namely: antioxidants 59.71% -76.83%, from 6.64 to 7.52% moisture content, ash content of 4.77% -6.66% and crude fiber 17.66% -24.02%. organoleptic properties: a sense of 3,06% -3,41%, 3,08% -3,48% aroma and color of 3,06% -3,25%. Herbal tea leaf is the best treatment young old nutmeg with a sun drying (MM).Keywords: Herbal tea of nutmeg’s leaf, nutmeg’s leaf, the age of nutmeg’s and the drying type, chemical organoleptic properties